Clinical performance of an analytically validated assay in comparison to microarray technology to assess PITX2 DNA-methylation in breast cancer. Issue 1 (December 2018) - Schricker, Gabriele; Napieralski, Rudolf; Noske, Aurelia; Piednoir, Elodie; Manner, Olivia; Schüren, Elisabeth; Lauber, Jürgen; Perkins, Jonathan; Magdolen, Viktor; Schmitt, Manfred; Ulm, Kurt; Weichert, Wilko; et al.
Abstract Significant evidence has accumulated that DNA-methylation of the paired-like homeodomain transcription factor 2 (PITX2 ) gene can serve as a prognostic and predictive biomarker in breast cancer. PITX2 DNA-methylation data have been obtained so far from microarray and polymerase chain reaction (PCR)-based research tests. The availability of an analytically validatedin vitro methylation-specific real-time PCR assay format (therascreen PITX2 RGQ PCR assay) intended for the determination of the percent methylation ratio (PMR) in the (PITX2) promoter 2 prompted us to investigate whether the clinical performance of these different assay systems generate comparable clinical outcome data. Mathematically converted microarray data of a previous breast cancer study (n = 204) into PMR values leads to a PITX2 cut-off value at PMR 14.73. Recalculation of the data to experimentally equivalent PMRs with the PCR PITX2 assay leads to a cut-off value at PMR 12 with the highest statistical significance. This cut-off predicts outcome of high-risk breast cancer patients to adjuvant anthracycline-based chemotherapy (n = 204; Hazard Ratio 2.48; p < 0.001) comparable to microarray generated results (n = 204; Hazard ratio 2.32; p < 0.0001). Thetherascreen PITX2 RGQ PCR assay is an analytically validated test with high reliability and robustness and predicts outcome of high-risk breast cancer patients to anthracycline-based chemotherapy.